Descriptions of new Tortricidae (Lepidoptera) reared from native fruit in Kenya - Razowski, Józef; Brown, John W. (Zootaxa, 2012)
One new genus, Concinocordis (Enarmoniini), and 13 new species, Phtheochroa aarviki (Cochylini), Endothenia ator(Bactrini), Concinocordis wilsonarum, Anthozela psychotriae (both Enarmoniini), Cosmetra podocarpivora, Cosmetrataitana, Gypsonoma scolopiae (all Eucosmini), Thaumatotibia salaciae, Cydia connara, Cydia sennae, Fulcrifera crota-lariae, Stenentoma sorindeiae, and Thylacogaster garcinivora (all Grapholitini), are described and illustrated. All speci-mens of these new species were reared from native fruit in Kenya. Two new combinations are proposed, Cydia anthracotis(Meyrick) (transferred from “Laspeyresia”) and Cosmetra nereidopa (Meyrick) (transferred from Sycacantha), and the female genitalia of Anthozela chrysoxantha Meyrick are illustrated for the first time.